Tantangan Implementasi Kurikulum Merdeka Pada Madrasah di Aceh Barat - Mulasi, Syibran; Jarjani Usman; Sri Suyanta; Musayyada, Musayyada (Seutia Hukamaa Cendekia, 2024)
Implementing the independent curriculum in the West Aceh District madrasah certainly poses challenges for teachers and the Ministry of Religious Affairs. On one hand, the independent curriculum strongly supports the development of students' potential. Still, there are obstacles, especially in meeting the requirements as supporters of implementing this curriculum. This study examines the challenges teachers and madrasah in West Aceh face regarding implementing the new curriculum. The research was conducted using a descriptive qualitative method, and data collection was done through observation, interviews with teachers and school principals, and individuals who could provide information on the implementation of the independent curriculum. The results of the study found that there were several challenges faced by madrasahs in the West Aceh District, including improving teacher competencies through training in teaching methods and understanding student differentiation to adapt learning to the talents and potentials of students, as well as in the field of approaches and teaching methods. Adequate facilities and infrastructure are needed to support the curriculum, and a comprehensive understanding is required for teachers approaching retirement to implement this curriculum effectively. In improving the quality of the implementation of the independent curriculum, cooperation from all parties is needed to evaluate each step in implementing this curriculum.